Requirements for Professional Teachers and Professional Teachers as Communicators and Facilitators - Wahyu Hidayati, Sri; Utama, Abdul Alimun (JUPE : Jurnal Pendidikan Mandala, 2024)
The group learning discussion method is one of the strategies to influence the motivation of students' interest in learning to be high. The existence of high interest in learning makes students study diligently and responsibly, which in the end is manifested in measurable and good student learning outcomes. This study aims to find out an overview of the factors that affect the learning motivation of students of the Civil Engineering, Informatics, and Electrical Engineering Study Program of Sumbawa University of Technology in the Islamic Religious Education Course. The type of research used is quantitative; descriptive with primary data types. Purposive sampling technique. Then the data collection technique in this study uses observation, interview, and documentation study guidelines.  Data analysis using data collection; data reduction; data presentation; and conclusions and verification. Based on these results, it is recommended to lecturers in religious education courses to strengthen the factors that motivate students during the educational process in an effort to increase the success of the students themselves